2010
DOI: 10.1021/jf103537a
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Environmental Behavior of the Chiral Herbicide Fenoxaprop-ethyl and Its Chiral Metabolite Fenoxaprop in Soil

Abstract: The enantioselective degradation behavior of fenoxaprop-ethyl (FE) and its chiral metabolite fenoxaprop (FA) in three soils under native conditions was investigated. Two pairs of enantiomers were analyzed by high-performance liquid chromatography (HPLC) with an amylose tri-(3,5-dimethylphenylcarbamate) (ADMPC) chiral column. The degradation of racemic FE in three soils showed the herbicidally inactive S-(-)-enantiomer degraded faster than the active R-(+)-enantiomer. FE was configurationally stable in soils be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 23 publications
2
35
0
Order By: Relevance
“…Many studies have shown that the enantioselectivity of chiral pesticides was significantly compound‐ and environment‐specific . Buerge et al found that the soil pH and redox conditions had great effects on the enantioselectivity of metalaxy, and alkalinization and acidification of a “nonenantioselective” soil prior to incubation resulted in enantioselective degradation, with the R ‐enantiomer and S ‐enantiomer preferentially degraded .…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that the enantioselectivity of chiral pesticides was significantly compound‐ and environment‐specific . Buerge et al found that the soil pH and redox conditions had great effects on the enantioselectivity of metalaxy, and alkalinization and acidification of a “nonenantioselective” soil prior to incubation resulted in enantioselective degradation, with the R ‐enantiomer and S ‐enantiomer preferentially degraded .…”
Section: Resultsmentioning
confidence: 99%
“…The (S)-enantiomers of aryloxyalkanoic acid herbicides and their esters are favorably degraded in aerobic soils, [78][79][80][81][82][83][84][85][86][87] but with no enantiomerization reported for the esters. 79,81,[85][86][87] In most cases, the degradation of each enantiomer is faster than the chiral conversion in either direction, and the (S) (R) conversion rate (k SR ) is larger than the opposite one (k RS ); such as k SR /k RS =1. 3 (4)].…”
Section: Microbial Degradation In Soilmentioning
confidence: 99%
“…It has been estimated that chiral pesticides account for over 40% of the total pesticides used in China, and that the proportion is expected to increase as compounds with more complex structures are registered for use. Enantiomers of chiral compounds, in spite of their very similar structure and appearance as a single compound in conventional analyses, can show very different toxicity, excretion, metabolism, and biological activities when exposed to asymmetric chemical or biological systems . In some cases, only one of the isomers of the pesticide is active, while the other may have less activity or even toxic effects against nontarget organisms .…”
Section: Introductionmentioning
confidence: 99%